Special issue on "Curriculum Planning and Implementation in Public Management Education for the 1990s"
Patricia A. Sto. Tomas coments the negligible impact of Public Management Education (PME) on the government bureaucracy, a Phenomenon which she partly attributes to the scanty number of PME graduates working in the government bureaucracy. She also exhorts the ASPAP member schools and the academe to reexamine the relevance of their respective PME curricula. Romeo B. Ocampo's work "Toward Philosophy of Public Management Education in the 1990s" lays the ground work for a solid foundation, upon which the science and art of administration can build on. He establishes some working propositions which may constitute parts of a Philosophy to guide the teaching of PME in the Philippine. Benito C. Cardenas writes on
Keywords: Teaching; Study; Education; Public Management; Public Administration; Public Administration - Study and Teaching - Philippines